Pelatihan E-Marketing Untuk Meningkatkan Peluang Usaha Melalui Media Sosial Pada Koperasi Wanita Atsiri Citayam - Lydia Salvina Helling; Adi Supriyatna; Indra Riyana Rahadjeng; Endang Wahyudi (Jurnal Pengabdian Pada Masyarakat, 2022)
E-MARKETING TRAINING TO INCREASE BUSINESS OPPORTUNITIES THROUGH SOCIAL MEDIA AT ATSIRI CITAYAM WOMEN’S COOPERATIVE. The Global Pandemic event that occurred in March 2020 had a major impact on all sectors of human life, especially the economic sector. Indonesia is one of the countries affected by the incident so its people are trying to find a way out amid the uncertainty of the world economy. The Ministry of Communication and Information Technology even urges micro, small and medium enterprises (MSMEs) to utilize digital technology in the marketing process. The Director of Information and Communication for the Economy and Maritime Affairs of the Ministry of Communication and Information said that more than 18% of MSMEs in Indonesia have entered the digital economy market, of which 37% of 60% are social media users. Members of the Citayam Bojonggede Atsiri Women's Cooperative are one form of MSMEs that are trying to hone their skills in marketing their products online. Social media is the most popular means of doing marketing with a wide range of people. In the Community Service Program conducted by the lecturers of the Bina Sarana Informatics University, training on the use of social media was given as a way to increase business opportunities amidst the ongoing Covid-19 pandemic. The training includes a brief presentation about e-marketing, explaining the importance of e-marketing in the midst of the current pandemic, providing several e-marketing options that are currently booming, and giving examples of how to promote on Facebook social media.